A multifactorial analysis of complex pharmaceutical platforms: an application of design of experiments to targetable polyacrylamide and ultrasound contrast agents†. (29th April 2015) - Bloch, Meital; Kenett, Ron; Jablonowski, Lauren; Wheatley, Margaret; Yavin, Eylon; Rubinstein, Abraham; Domb, Abraham; Slomkowski, Stanislaw
<x xml:space="preserve">Abstract</x> To improve visualization of malignant regions in the colon epithelium during diagnostic procedures, we have recently suggested a multimodal system comprising the water‐soluble cationized polyacrylamide, tagged with the near infrared dye derivative IR‐783‐S‐Ph‐COOH [fluorescent‐cationized polyacrylamide (Flu‐CPAA)] and conjugated to the recognition peptide VRPMPLQ to form Flu‐CPAA‐Pep. The fluorescent‐cationized polyacrylamide‐peptide conjugate (Flu‐CPAA‐Pep) is then incorporated into echogenic microbubbles (MBs) made of polylactic acid (PLA) to protect it from pre‐mature interactions with plasma proteins upon intravenous administration. It is expected that under directed ultrasound interrogation the Flu‐CPAA‐Pep cargo would be released in the region of interest, as a result of the MBs rupture into submicron PLA fragments (SPF). Due to their nanoscale dimension, the SPF will escape from the vasculature and allow a specific binding of the Flu‐CPAA‐Pep to the suspected malignant tissue. The complex nature of the system requires a multifaceted statistically based experimental design. Here we apply a design of experiment methodology to enable effective screening of key parameters in our experimental setup. It enables the assessment of the role of the different formulation parameters by identifying statistically significant interactions as observed in vitro (cell lines) and in vivo (colon cancer‐induced rat model). Particularly important was the identification of the interaction between the fraction (mol%) of the cationic monomer in the Flu‐CPAA and (a) the presence of recognition peptide as assessed in the in vitro experiments and (b) the use of a presenting platform (whether MBs or SPF) as assessed in the in vivo experiments. Copyright © 2015 John Wiley & Sons, Ltd.